Elementary. The fifth season [videorecording (DVD)] - Doyle, Arthur Conan, 1859-1930 (CBS DVD ; Paramount, 2017)
The erratic, unpredictable, and intellectually incomparable detective Sherlock Holmes cracks case after case for the NYPD with the help of his ever-reliable partner Joan Watson. The balance of this time-tested team shifts as Holmes and Watson face difficult personal choices and impossible crimes. From a murderous drug gang to a rogue intelligence agency, the threats have never been starker. And from snake venom-laced meals, to invisible gunshots, the methods have never been stranger.